The Role Of Financial Statements On Increasing Income In SMEs - Saimajuli Sahro Harahap; Abdul Halim; Yudi Prayoga (International Journal Of Community Service, 2022)
PKM (Community Service) activities carried out by the author in Kampung Kampung Baru Promise West Bar District together with Small and Medium Enterprises (UKM). The purpose of this Community Service Activity is to provide knowledge and understanding of the recording of financial statements in a simple and structured manner. Financial reports that function as a tool to analyze financial performance that can provide information about financial position, so that it can be used as a basis for decision makers in increasing income for SMEs and providing opportunities for SMEs to develop their businesses. The implementation method is to make observations that identify SME actors who have not recorded financial statements in a simple and structured manner. For the results, assistance and socialization were carried out which invited several SME players and startup business actors as many as 21 participants. In the implementation of this companion and socialization, it shows that the importance of recording financial statements for SMEs in increasing income for each period of recording financial statements. After the mentoring and socialization, the authors distributed questionnaires to measure the knowledge and understanding of the participants and the results showed that 78% of the participants already knew what financial reports were and understood how to make simple financial reports for their business.